2021
DOI: 10.1042/bsr20210055
|View full text |Cite
|
Sign up to set email alerts
|

Early B-cell factors involve in the tumorigenesis and predict the overall survival of gastric cancer

Abstract: Gastric cancer (GC) is a heavy health burden around the world, which is the fifth most frequent tumor and leads to the third most common cancer-related deaths. It is urgent to identify prognostic markers as the guideline for personalized treatment and follow-up. We accessed the prognostic value of Early B cell factors (EBFs) in GC. 415 GC tissues and 34 normal tissues from TCGA-STAD, 616 external patients from GSE15459, GSE22377, GSE51105, GSE62245 were enrolled for analysis. Univariate and multivariate Cox re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Other studies also illustrated a prognostic model for GC patients. Wang et al 8 revealed that early B cell factors are prognostic biomarkers for GC patients, and 5-fluorouracil, methotrexate, and vorinostat are suitable to inhibit the function of early B cell factors and suppress the process of tumorigenesis. Li et al 9 developed a prognostic model, IDOScore, based on the expression levels of TAP2, SERPINB5, LTBP1 and LAMC1.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies also illustrated a prognostic model for GC patients. Wang et al 8 revealed that early B cell factors are prognostic biomarkers for GC patients, and 5-fluorouracil, methotrexate, and vorinostat are suitable to inhibit the function of early B cell factors and suppress the process of tumorigenesis. Li et al 9 developed a prognostic model, IDOScore, based on the expression levels of TAP2, SERPINB5, LTBP1 and LAMC1.…”
Section: Introductionmentioning
confidence: 99%